Diamond Drill-bit Seismic-While-Drilling Velocity Analysis Using Semblance and MUSIC from Hillside, South Australia - Sun, Bai Chun; Bona, Andrej; King, A.; Zhou, B. (EAGE, 2014)
In this paper, we demonstrate the resolution differences between MUSIC and semblance using synthetic examples. Both methods are applied to detect coherent move-out from the drill-bit. The coherency can be used to obtain an updated velocity information around the bore hole. The velocity is estimated based on approximately known drill-bit position. We also perform the drill-bit imaging using coherent cross correlation migration. We illustrate the two methods with synthetic examples and a field data example from diamond drill-bit SWD experiment at Hillside (South Australia).